Novel cell separation method for molecular analysis of neuron-astrocyte co-cultures - Goudriaan, Andrea; Camargo, Nutabi; Carney, Karen; Oliet, Stéphane H.; Smit, August B.; Verheijen, Mark H. (Frontiers in Cellular Neuroscience, 2014)
Over the last decade, the importance of astrocyte-neuron communication in neuronal development and synaptic plasticity has become increasingly clear. Since neuron-astrocyte interactions represent highly dynamic and reciprocal processes, we hypothesized that many astrocyte genes may be regulated as a consequence of their interactions with maturing neurons. In order to identify such neuron-responsive astrocyte genes in vitro, we sought to establish an expedited technique for separation of neurons from co-cultured astrocytes. Our newly established method makes use of cold jet, which exploits different adhesion characteristics of subpopulations of cells (Jirsova etal., 1997), and is rapid, performed under ice-cold conditions and avoids protease-mediated isolation of astrocytes or time-consuming centrifugation, yielding intact astrocyte mRNA with approximately 90% of neuronal RNA removed. Using this purification method, we executed genome-wide profiling in which RNA derived from astrocyte-only cultures was compared with astrocyte RNA derived from differentiating neuron-astrocyte co-cultures. Data analysis determined that many astrocytic mRNAs and biological processes are regulated by neuronal interaction. Our results validate the cold jet as an efficient method to separate astrocytes from neurons in co-culture, and reveals that neurons induce robust gene-expression changes in co-cultured astrocytes.